2019
DOI: 10.18502/jebhpme.v3i4.2064
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Required Number of Nurses in Emergency Department of Imam Ali Hospital Affiliated by Alborz Province Using WISN Method

Abstract: The provision of manpower is one of the effective factors on the improvement in the coverage of health services and the realization of the highest community health level and a considerable part of the health budget is devoted to the production and update on human resources. Therefore, the current study aimed to estimate the number of nurses required in the Emergency Department (ED) of Imam Ali hospital based on the proposed method of the World Health Organization, in which the manpower is calculated based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A study conducted in a teaching hospital in Iran showed a shortage and high work pressure of health care staff working in emergency departments [ 41 ]. Literature also suggests that emergency departments are usually understaffed whether assessed by WISN or otherwise [ 41 43 ]. In the context of Pakistan and KP particularly, these EDs work as evening OPDs and the patients usually present with minor ailment and complaints which causes an unnecessary workload in the EDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in a teaching hospital in Iran showed a shortage and high work pressure of health care staff working in emergency departments [ 41 ]. Literature also suggests that emergency departments are usually understaffed whether assessed by WISN or otherwise [ 41 43 ]. In the context of Pakistan and KP particularly, these EDs work as evening OPDs and the patients usually present with minor ailment and complaints which causes an unnecessary workload in the EDs.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study show that all the tertiary care hospitals had an acute shortage of nurses with high workload pressure. Nurses more than any other cadre of health care providers are affected by the size, skills, and mix [ 34 , 43 ]. Complementing the result of our survey, several studies both in developing and developed countries have reported an acute shortage of nurses working at every level of the healthcare delivery system [ 34 , 36 – 39 , 41 43 , 45 ], Studies have shown that nurses have higher workload pressure as compared to doctors which indicates relatively fewer nurses as compared to doctors in the many healthcare delivery systems [ 36 – 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hospital is one of the means of health efforts that organizes health service activities [1], which play a role in supporting the achievement of an optimal public health degree. One of the health service efforts carried out by the hospital is inpatient services.…”
Section: Introductionmentioning
confidence: 99%
“…One of the health service efforts carried out by the hospital is inpatient services. Hospitalization is one of the dominant factors of hospital services and is a very significant financial income for the continuity of the hospital organization in the future, so it is necessary to make efforts to improve the quality in health services [1]- [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the nursing staff shortage is observed and this shortage caused a high working pressure on the nurses working in the study area. Considering the vital role of nurses in the emergency department, it is recommended to employ and distribute the manpower based on the requirement and workload in the department (14). The purpose of study of Noprianty et al (2020) was to determine the analysis of the needs of nurses based on the WISN method.…”
Section: Introductionmentioning
confidence: 99%